The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jzs.12048
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific genetic variation in the common midwife toad (Alytes obstetricans): subspecies assignment using mitochondrial and microsatellite markers

Abstract: The common midwife toad (Alytes obstetricans), widely distributed in the northern half of the Iberian Peninsula and part of Western Europe, is currently subdivided into four subspecies: A. o. obstetricans, A. o. boscai, A. o. pertinax and A. o. almogavarii. However, the delimitation of these subspecies and their ranges are still under discussion because strong discordances have been found between morphological and molecular data, and especially among different genetic markers. Here, we screen a set of novel mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Our analysis of genetic diversity in A. obstetricans revealed very high levels of intraspecific variation in Iberia, in agreement with previous results based on allozymes (Arntzen and García-París, 1995), morphology , and mtDNA and nuclear markers (Fonseca et al, 2003;Martínez-Solano et al, 2004;Gonçalves et al, 2007;Maia-Carvalho et al, 2014a). The common midwife toad has been previously considered as including four essentially parapatric subspecies in the Iberian Peninsula (A. o. obstetricans, A. o. boscai, A. o. pertinax, and A. o. almogavarii; see Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our analysis of genetic diversity in A. obstetricans revealed very high levels of intraspecific variation in Iberia, in agreement with previous results based on allozymes (Arntzen and García-París, 1995), morphology , and mtDNA and nuclear markers (Fonseca et al, 2003;Martínez-Solano et al, 2004;Gonçalves et al, 2007;Maia-Carvalho et al, 2014a). The common midwife toad has been previously considered as including four essentially parapatric subspecies in the Iberian Peninsula (A. o. obstetricans, A. o. boscai, A. o. pertinax, and A. o. almogavarii; see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…First, the location of the northern boundary between A. o. boscai and A. o. obstetricans had been inferred to be in the Pyrenees, based on allozyme data (Arntzen and Szymura, 1984), but was shown to be more likely located in the Iberian northwest, somewhere between northern Portugal and the Cantabrian Mountains. Second, Maia-Carvalho et al (2014a) revealed the existence of two well-differentiated groups within A. o. boscai, separated by the Douro River, as suggested by Fonseca et al (2003). Additionally, the recent multilocus assessment of phylogenetic relationships in Alytes by Maia-Carvalho et al (2014b) produced inconclusive results about the relationships between major clades in A. obstetricans and indicated conflict with the current morphology-based subspecific taxonomy.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…To examine whether previously described subspecies actually represent unique evolutionary lineages, many attempts have been made using a variety of conventional and modern methods, including quantitative morphological analyses and molecular phylogenetic analyses (e.g. Glor and Laport 2012;Hawlitschek et al 2012;Maia-Carvalho et al 2014;Sackett et al 2014). Although the necessity or efficacy of the subspecies as a taxonomic rank has been repeatedly questioned (Hillis 1992;Burbrink et al 2000;Zink 2004), taxonomic studies in search of definable subspecies with multiple methods have contributed to the establishment of universal criteria of the subspecies rank (Sackett et al 2014;Torstrom et al 2014).…”
Section: Introductionmentioning
confidence: 99%